LITERATURE REVIEW: IMPLEMENTATION OF TRAINING AND SKILL DEVELOPMENT IN IMPROVING HUMAN RESOURCE (HR) COMPETENCE AT CV HANAN DOYAN JAJAN (HDJ) GROUP, UJUNG BERUNG, BANDUNG - Kartini, Amy; Tresnawati, Amilia (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study aims to analyze the implementation of training and skill development in improving the competence of Human Resources (HR) at CV HDJ Group. In an era of increasingly tight business competition, improving the quality of HR is a crucial factor in supporting the success of the company. The research method used is a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation of employees and management of CV HDJ Group. The results of the study indicate that the training and skill development program implemented by the company plays a significant role in improving employee competence. The program includes technical training, soft skill development, and coaching in the form of mentoring and coaching. Employees who participate in this program show increased performance, productivity, and ability to complete their tasks and responsibilities better. However, this study also found several challenges, such as limited training time and lack of post-training evaluation. Therefore, it is recommended that CV HDJ Group increase the frequency and duration of training and conduct ongoing evaluations to measure the effectiveness of the program.